The Factors and Detrimental Impact Of Parent Divorce - Bahagia Bahagia; Leny Muniroh; Abdul Karim Halim; Rimun Wibowo; M Azhar Al Wahid; Zakky Muhammad Noor (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Divorce becomes a reality in life even though neither husband and wife want this problem to occur. This study aims to find the causes of divorce and the impact of divorce on children. The research method used is the literature review method or a method that does not use the field method but uses a variety of existing literature in the library and sources from articles. Data collection is done by directly collecting scientific articles from empirical research, recording findings, and analyzing each finding. At the same time comparing the findings of previous studies. The results showed that divorce did not occur immediately but there were triggers including economic problems and environmental problems. The troubled economy will also affect disharmony in the household because it is related to meeting needs. Money is not everything but money is needed to buy basic needs when basic needs are not met continuously it can lead to divorce. Coupled with the infidelity between a husband and wife with another person who becomes the third person, it triggers conflict and leads to divorce. The impact on children is that children do not get love, motivation to learn can be low, sad, lonely, and learning achievement decreases. Although there are children who are increasingly enthusiastic in the midst of the problems they are experiencing